Protection of HVDC Transmission Systems for Integrating Renewable Energy Resources - Zaky, Mohamed S.; Ahmed, Hossam E.; Elsadd, Mahmoud; Elgamasy, Mahmoud (Engineering, Technology & Applied Science Research, 2023)
This paper introduces a fault locator approach designed for non-homogeneous VSC-HVDC (Voltage Source Converter-High Voltage Direct Current) transmission circuits. In various projects, such as those involving offshore wind farms, the transmission circuit’s right-of-way can be non-homogeneous, incorporating a mix of underground cables and overhead lines. This diversity in circuit configuration poses issues with fault location approaches. The proposed method involves measuring signals at two sides of the non-homogeneous transmission circuit. Initially, the faulted section is identified using a specific criterion. This criterion calculates the profile of the 1-mode component of the voltage along the transmission circuit, without considering its non-homogeneous nature. This method is founded upon disparities in the voltage change rate between power cables and overhead lines. The provided identification method does not depend on the calculation of fault distances. Subsequently, the faulty point within the selected section is obtained by updating the calculated voltage profile. Notably, our method does not necessitate the installation of additional sensors at junction points. Furthermore, the introduced approach has the capability to locate various fault types, including pole-to-pole and pole-to-ground faults, and it remains effective regardless of the fault resistance value. These investigations were conducted using PSCAD software as a simulation environment, with the proposed method’s calculations executed in MATLAB.